Evaluation of eustachian tube function in chronic suppurative otitis media with reference to its treatment outcome - Gupta, Sucheta; Goel, Mohit; Jamwal, Padam Singh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: The study was undertaken to find out Eustachian tube function in safe type of chronic suppurative otitis media and to study the comparison of graft uptake in normal, partially impaired and grossly impaired Eustachian tube function in safe type of chronic suppurative otitis media. Methods: The present prospective study was conducted in the Department of Otorhinolaryngology and Head and Neck surgery, Sri Maharaja Gulab Singh Hospital, Jammu during the period from November 2016 to October 2017. Patients were diagnosed clinically and also audiometrically by pure tone audiometry and impedance audiometry. Eustachian tube function test- Toynbee test was done in all the patients. Results: Out of 20 patients with normal Eustachian tube function, 19(95%) showed graft uptake. Out of 20 patients with partially impaired Eustachian tube function, 18 (90%) showed graft uptake. Out of 20 patients with grossly impaired Eustachian tube functions 13 (65%) showed graft uptake. Comparison of mean values of pre and post- operative air-bone (AB) gap with respect to normal, partially impaired and grossly impaired Eustachian tube functions is highly significant statistically with (p<0.001). Conclusions: As seen in our study, functioning Eustachian tube is an important requirement for optimum outcome of myringoplasty. Testing the functions of Eustachian tube before surgery provides a possibility of predicting the possible outcome of myringoplasty or tymapanoplasty. This is also concluded that a partially functioning Eustachian tube should not be considered to be a contraindication to these surgeries as in many of these cases graft uptake and AB gap closure was good (90%).